The Model of Teacher’s Tolerant Behaviour as the Means for the Humanization of the Pedagogical Process - Chehlovs, Mihails; Chehlova, Zoja; Rossolova, Tatiana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Humanization is the key educational strategy in a democratic society. According to the principles of the Council of Europe, the mission of education is to help everyone to develop his/ her individual potential and become a citizen of the European Community, to understand interconnectedness with Europe and the rest of the world. In accordance with the concept of common European culture, young people have to be able to understand the contemporary world and adapt to constant changes, work actively and creatively, continue learning, explore problems, cooperate and perfect themselves (Ross,2006). Scholars agree that the humanization of education is a necessary precondition in order to educate an active personality. The object of research - the models of teacher’s behaviour in the educational process. The subject of research – the humanization of the pedagogical interaction between the teacher and learners. The aim of the research – to determine conditions concerning the humanization of pedagogical interaction between the teacher and learners and to approbate them in practice in the classes of pedagogy. Research methodology – to use approaches: humanitarian, personal activity, cultural; methods: testing, questionnaire, interviewing, mathematical statistics.